ETHNOGRAPHIC STUDY: "UMAH PITU BUNTUL LINGE SPACE" AS A GAYO CULTURAL HERITAGE IN CENTRAL ACEH REGENCY - Khairani, Cut; Nurdinsyah, Nurdinsyah; Fitrah, Hariki (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The preservation of cultural heritage is vital for maintaining the identity of indigenous communities. Purpose: This study explores the function and motifs of the seven spaces in the Umah Pitu Buntul Linge, a traditional Gayo house in Central Aceh Regency, and its significance as a cultural heritage. Method: Using a qualitative ethnographic approach, data were collected through documentation and observation. Result: The findings reveal that each of the seven rooms serves a distinct purpose related to governance and problem-solving in the Linge Kingdom, with motifs that symbolize specific functions and customs. The study highlights the philosophical meanings embedded in the building's design and the openwork motifs, which reflect Gayo cultural values. Conclusion: This research underscores the importance of preserving the Umah Pitu Buntul Linge as a symbol of Gayo identity and local wisdom